What are the Odds that Tetanus is an Endogenous Infection? - Salerian, Alen J (European Journal of Applied Sciences, 2025)
Tetanus is an infection caused by Clostridium tetani characterized by fever, cramped-up jaw, muscle spasms, headache, seizures, sweating, and trouble swallowing 3–21 days following exposure. About 10% of cases prove to be fatal. C. tetani produce toxins that interfere with normal muscle contractions. Some infections seem to be both heritable and endogenous contradicting the traditional infection paradigm consistent with the germ theory-and contamination as the exclusive pathway of infection. Objective: To project the mathematical odds of “ Tetanus is endogenous”. Method: We applied the probability theory to relevant data to project, the mathematical odds of certainty that “Tetanus is endogenous” . Results: Eight observations consistent with” tetanus is endogenous “and inconsistent with” tetanus is not endogenous” suggests the mathematical certainty that “tetanus is endogenous” is % 99.7. Discussion: Converging evidence suggest some tetanus infections may represent endogenous infections that are produced independent of contamination. At present we do not know the precise biological processes involved in causing tetanus. Conclusion: Some tetanus infections maybe endogenous. Highlights: Tetanus is caused by Clostridium tetani characterized by muscle spasms, fever and seizures. Endogenous infections may develop through pathways independent of contamination. Animals and humans harbor clostridium tetani without sickness. Clostridium tetani is almost always associated with traumatic injuries. Neonatal tetanus (trismus nascentium) occurs from healthy mothers(5). The dramatic difference of incidence of tetanus between developed and developing countries for neonatal tetanus but not for tetanus suggests immunity by vaccination against the toxin produced by Clostridium tetani. Mathematical certainty that tetanus is endogenous= % 99.9